RASIONALISASI INISIATOR PROGRAM PELESTARIAN BAHASA BALI DI KOTA DENPASAR - Putra, Nararya Prasetya; Kebayantini, Ni Luh Nyoman; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
This study analyzes and describes how the types of social action and rationalization process carried out by the initiator in organizing the program Utsawa Bali Shanti, Utsawa Dharma Budaya and Contest Nyurat Balinese Aksara in Denpasar City. The method used in this research is qualitative descriptive explanative. The theory used is Maximilian Weber's theory of social action. These three actions have various motives which show subjective meaning to the initiator. In addition, there are also two types of rationalization processes carried out by the initiator, namely the means-end rationality and the value rationality. Keywords: Balinese language preservation program, rationalization, social action, initiator.